Exploration of bison industry practices and mitochondrial metabolism - Velazco, David, author; Nair, Mahesh, advisor; Edwards-Callaway, Lily, advisor; Hess, Ann, committee member; Engle, Terry, committee member (Colorado State University. Libraries, 2024)
The objectives of this study were to benchmark the United States bison meat industry and to compare the mitochondrial metabolism of beef and bison. The first project evaluated bison industry stakeholder perceptions on management, animal welfare, and meat quality with in-person and online surveys. The stakeholder surveys identified animal handling, bison behavior, employee training, facility design, and transportation duration as the most critical factors that could impact animal welfare in the bison production system. The stakeholders understood that animal welfare is a crucial component of bison production and directly affects meat quality. The second project analyzed multiple live animal factors to benchmark their influence on specific meat quality attributes. Live animal production parameters of bison (n = 2,284; Bulls n = 1,101; Cows n = 199; Heifers n = 984) such as distance traveled, season, number of head bumps in the chute, sex class, and live weight were associated (P < 0.05) with differences in fat thickness, ribeye area, blood splash presence, and instrumental color of bison meat. The third experiment compared the mitochondrial metabolism of bison and beef. The left side masseter muscle of crossbred Angus steers (n = 12) and bison (n = 12) were collected within 60 minutes postmortem. The oxygen consumption rate of permeabilized muscle fibers at specific respiration states was evaluated utilizing the Oroboros O2K high-resolution respirometry system. The abundance of electron transport chain protein in bison and beef muscle was measured using gel electrophoresis. All mitochondrial data were analyzed as mixed models with species as the fixed effect, and day confounded with sex class as the random effect, using JMP Pro 16. No differences were found in oxygen consumption flux (JO2) between bison and beef under baseline, Leak respiration (LEAK; P = 0.8813), rotenone respiration (ROT; P = 0.1071), and carbonyl cyanide m-chlorophenyl hydrazone respiration (CCCP; P = 0.7502) respiration states. Bison permeabilized muscle fibers had a higher (P = 0.0016) JO2 during max OXPHOS (+D) and produced more hydrogen peroxide (P = 0.0234) during this respiration state compared to beef. Respiration control rate (RCR) did not differ (P =0.2928) between beef and bison permeabilized muscle samples. Bison muscle samples contained lower relative abundance of the electron transport chain complexes II (P = 0.0057) and III proteins (P = 0.0020) than beef. Additionally, bison and beef had similar concentrations of citrate synthase in the masseter muscle (P = 0.4650). Results from these experiments can be used as an industry reference to monitor improvements in bison animal welfare and meat quality. Additionally, information regarding mitochondrial metabolism can serve as the foundation for future research to further investigate differences in efficiency between bison and beef.
Keywords: meat; welfare; mitochondria; bison